The Effectiveness of Social Media Use on Gen Z Communication Patterns in The Digital Era - Dara Nurhaliza Prihantira, Shafira; Dharmawan, Leonard (IJESS International Journal of Education and Social Science, 2025)
The development of digital technology has significantly changed people's communication patterns, especially among Gen Z, known as the digital native generation. This study aims to analyze the effectiveness of social media utilization on the communication patterns of students in the Digital Communication and Media Study Program, IPB Vocational School. The research approach used was quantitative with a survey method of 179 respondents. Data collection techniques were carried out through online questionnaires, while data analysis techniques included descriptive statistical tests, multiple linear regression tests, and hypothesis testing to examine the influence of independent variables on communication patterns. The results of the study indicate that social media utilization has a significant influence on student communication patterns, especially in aspects of interactivity, accelerating information dissemination, and expanding communication reach. Platforms such as Instagram, TikTok, and YouTube play an important role in supporting students to interact more effectively in the digital era. Individual characteristics such as age, gender, and pocket money do not have a significant influence on student communication patterns. Based on the results of the regression test, the variable of social media utilization has a significance value <0.05, which indicates a real influence on students' digital communication patterns. This study concludes that social media contributes positively in facilitating communication in the digital era, especially for digital communication and media students. Optimizing the wise use of social media is expected to improve the effectiveness of academic and social communication. Research recommendations suggest that students utilize social media productively and educational institutions integrate digital platforms into the learning process to support more interactive and efficient academic interactions.